Phytoclimatic Stages and Vegetation in Baden - Württemberg and Emilia - Romagna - Dario Botti (Landscape Online, 2019)
The assessment of ecosystems and landscapes requires reliable and simple tools. Climate determines broad type and distribution of ecosystems. Therefore, it is a major factor to consider in environmental analysis and ecological regionalization. A standardized bioclimatic classification would be useful to characterize and compare different ecosystems. In this paper, Defaut’s Phytoclimatic System (DSPS) was tested at regional scale in two European areas: Baden-Württemberg (Germany) and Emilia-Romagna (Italy). DSPS phytoclimatic units and vegetation belts and climatic parameters are illustrated and discussed. In addition, as an example application, a map of phytoclimatic units of Emilia-Romagna is designed. Some challenges in matching vegetation to DSPS were found: 1) in areas where transition from one stage to another are not sharply delineated and different vegetation types are intermixed; 2) in alluvial lowlands; 3) in heavily anthropized areas. In conclusion, the results of this study suggest that DSPS can be a useful tool in ecological regionalization and in landscape analysis.